Phonological verbal fluency norms for Spanish-speaking middle-aged and older adults: Letters F, A, and S - Rubio-Valdehita, Susana; López-Higes, Ramón; Montenegro-Peña, Mercedes; Delgado-Losada, María Luisa (Anales de Psicología / Annals of Psychology, 2026)
Background: Verbal fluency tests are easy and regularly used in neuropsychological assessment. This paper offers normative data of phonological verbal fluency tests (FAS) for Spanish middle- and older-aged adults, considering sociodemographic factors, and different measures such as the total number of words, errors, and words evoked in each 15 sec-segment. Method: A total of 920 cognitively unimpaired participants, aged between 50 and 89 years old, participated in the study. The statistical procedure includes the conversion of percentile ranges into scalar scores to obtain a normal distribution. The effects of age, education, and sex were verified by determination coefficients. Corrections were only applied for those sociodemographic variables that explained more than 5%. Linear regressions are used to calculate the scalar-adjusted scores. Results: Scalar scores and percentiles for all tests across different measures are shown. Supplementary tables are provided for necessary adjustments considering educational level, since the results showed no differences related to age and sex across analyses. Conclusions: This study provides updated and clinically useful normative data for European Spanish-speaking natives, aged from 50 to 89 years, for FAS tests, considering errors and word production over 15-second segments. The influence of education on tasks aligns with findings from previous studies.